PERVASIVE MAGNESIUM LOSS BY MARINE WEATHERING OF PERIDOTITE - Snow J.E.; Dick H.J.B. (My University, 1995)
Bulk abyssal peridotites have lower MgO and higher SiO2 than comparable continental peridotites. If these low MgO2 ratios were a primary feature of the oceanic mantle, a major re-evaluation of the concentrations of these elements in the bulk silicate Earth would be necessary. Alteration mechanisms documented until now in abyssal peridotites (amphibolite facies metamorphism and serpentinization) are nearly isochemical (besides water), and thus do not explain such widespread compositional differences.We investigate here the possibility that the low MgO2 ratios are due to a different type of alteration. We have measured bulk compositions in a suite of abyssal peridotites and compared these to their primary compositions, measured where possible or estimated. It is clear that the compositional differences between continental and abyssal peridotites are an alteration phenomenon. It is likely that they are not a result of serpentinization, but of pervasive weathering, below about 150°C (the temperature below which seawater is undersaturated with Mg-rich minerals), and at water/rock ratios between 103 and 105. The average dredged abyssal peridotite appears to have lost about 5 wt% MgO.Peridotite is an important component of the ocean crust. Its chemical behavior during alteration thus has a large impact on global mass budgets for many elements. A preliminary estimate of the magnitude of Mg loss from the ultramafic part of the ocean crust shows the maximum contribution to the oceans (1012 moles Mg/y) to be significant, nearly 85% of the yearly Mg flux from rivers. Such an input of Mg to the oceans from peridotites would require that Mg-based estimates of the total hydrothermal flux be revised upward.